2005
DOI: 10.2174/1573406054368701
|View full text |Cite
|
Sign up to set email alerts
|

New non-peptidic Inhibitors of Papain Derived from Etacrynic Acid

Abstract: Cysteine proteases are connected to various viral and parasitic infections, as well as to other severe diseases like arthritis, stroke and cancer. Due to its alpha,beta-unsaturated carbonyl moiety etacrynic acid, a well known diuretic, can inhibit cysteine proteases in a Michael-type reaction by reaction with the nucleophilic cysteine residue of the active site. For first structure-activity-relationship studies modifications at various positions of the etacrynic acid structure have been investigated concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…89 Among the isolated compounds, biflavone amentoflavone (86) was recognized as a potent noncompetitive inhibitor, exhibiting an IC 50 value of 8.3 μM. An SAR study demonstrated the three authentic flavones, apigenin (90), luteolin (82), and quercetin (83), showed inhibitory activities (IC 50 ) of 280.8, 20.2, and 23.8 μM, respectively. The activity of amentoflavone (86) was consistent with the binding interactions (docking studies of 86 with PDB ID 2Z3E, see SI, Figure S6), with Val186 and Gln192 as one of the key binding modes with the target site.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…89 Among the isolated compounds, biflavone amentoflavone (86) was recognized as a potent noncompetitive inhibitor, exhibiting an IC 50 value of 8.3 μM. An SAR study demonstrated the three authentic flavones, apigenin (90), luteolin (82), and quercetin (83), showed inhibitory activities (IC 50 ) of 280.8, 20.2, and 23.8 μM, respectively. The activity of amentoflavone (86) was consistent with the binding interactions (docking studies of 86 with PDB ID 2Z3E, see SI, Figure S6), with Val186 and Gln192 as one of the key binding modes with the target site.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…[11]), its norethyl derivative (12, for synthesis, see the Supporting Information), trans-(1-phenyl)but-2-en-1-one (9, Sigma-Aldrich), 3-methylenechroman-4-one (10, synthesized according to ref. [38]), and 6-chloro-4H-chromen-4-one (11,Maybridge). The structures of these compounds are shown in Figure 3.…”
Section: Chemoassaysmentioning
confidence: 99%
“…Another approach starts from substituted etacrynic acid, [10,11] which possesses an a,b-unsaturated ketone moiety as an electrophilic building block ( Figure 1). While the vinylogous esters lead to irreversible inhibition, the etacrynic acid derivatives show only reversible inhibition of proteases.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of inhibition mechanism, ethacrynic acid derivatives are a new interesting class of inhibitors [166,167]. The compounds are derived from the well known diuretic drug [168].…”
Section: Inhibitors Containing An Activated Double Bond: Methylene Kementioning
confidence: 99%
“…These interesting properties of ethacrynic acid led to the development of derivatives thereof as potential non-peptidic cysteine protease inhibitors [166][167]. To investigate which structural features are necessary for inhibition, the prototype compound was modified on several positions and tested on various proteases (Fig.…”
Section: Inhibitors Containing An Activated Double Bond: Methylene Kementioning
confidence: 99%